Liberdade Assistida e redes de sustentação: trajetórias de uma adolescente - Gil, Ana Carolina Martins (2017)
This dissertation aims to discuss the socioeducative program called “liberdade assistida” - assisted freedom by analyzing the trajectories of a adolescent who has passed through it, investigating whether the program constituted support network for the adolescent. Therefore, we chose to work with the characterization and analysis of the trajectories of the adolescent before and after accomplishing the program. For the construction of the trajectory, we selected interviews with the adolescent and observed her life routines, since we chose to work with the girl in different places where she moved in 2016, in a coastal city in Sao Paulo state. The construction of a trajectory map together with the adolescent was another research strategy. To fulfill the aims proposed, this dissertation is organized in three chapters. The first chapter discusses the socioeducative program of assisted freedom, focusing the place of the networks in its implementation and the place of the adolescent women in the socioeducative system, based on the literature review of the field. The theoretical-methodological perspective that guided this work, focused on the Institutional Analysis, and the analysis of the researcher's implication in the connection with the adolescent are the theme of the second chapter, especially since the researcher was a teacher of the adolescent in the process of compliance with the program. The narratives of the adolescent, the itinerary map and the researcher's records in the field diary included the study of her trajectories, her support networks and her singular searches, presented in the third chapter around two axes: 1) Freedom Assisted, its function and its network effects; 2) The nets of life on the streets. The results of this research are added to other researches related to this theme in a perspective to stablish a diagnosis of the socio-educational program: devoid of resources, of a sanctioning nature, with fragmented actions and little power to sustain the network, the measure becomes an unassisted freedom for the adolescent author of an infraction